Does interpersonal sensitivity and paranoid ideation predict nomophobia: an analysis with a young adult sample - YILMAZ, TUĞBA (My University, 2022)
Nomophobia has been studied extensively due to its negative effects on human health and psychology. In terms of clinical psychology, nomophobia has been linked consistently to depression and anxiety. Studies also investigated whether it is a dependency, an impulse control problem, an obsession or a phobia; however, no clear clinical representation was confirmed. Although it was proposed to be added as an official diagnosis to DSM-5, these attempts were inconclusive. In this study, nomophobia was examined clinically by SCL-90 factors. A hierarchical regression analysis was performed by controlling anxiety, depression, phobia and obsessions by putting them in the first step. At the next step, paranoid ideation was entered while interpersonal sensitivity was introduced at the last step. The variables were assigned according to the steps according to their connections confirmed by the literature, the correlation coefficients and beta weights obtained in the current study. The hierarchical regression analysis confirmed that after controlling anxiety, depression, phobia and obsessions, nomophobia is explained by interpersonal sensitivity. Paranoid ideation is also an important variable in step 2, but it lost its significance in the last step. Nevertheless, it was thought that what makes people sensitive to interpersonal issues is a kind of fear of missing out others\" experiences (FoMO) which is related to nomophobia. This fear of missing out might prepare people to constantly check on mobile phones thinking paranoid about what they might have been missing or deprived of. Clinical implications and limitations were discussed.
Keywords: Sosyal ve Beşeri Bilimler; Psikoloji; Social Sciences and Humanities; Psychology; PSİKOLOJİ, MULTİDİSİPLİNER; Temel Bilimler (SCI); PSYCHOLOGY, MULTIDISCIPLINARY; PSYCHOLOGY; Natural Sciences (SCI); Psikoloji (çeşitli); Genel Psikoloji; Sosyal Bilimler ve Beşeri Bilimler; Psychology (miscellaneous); General Psychology; Social Sciences & Humanities; Nomophobia; Interpersonal sensitivity; Paranoia; Fear of missing out (FoMO); Clinical psychology; Psychopathology; Nomophobia; Interpersonal sensitivity; Fear of missing out (FoMO); Clinical psychology; Psychopathology